2018
DOI: 10.1186/s12931-018-0816-x
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effect of mesenchymal stem cells on pulmonary myeloid cells following neonatal hyperoxic lung injury in mice

Abstract: BackgroundExposure to high levels of oxygen (hyperoxia) after birth leads to lung injury. Our aims were to investigate the modulation of myeloid cell sub-populations and the reduction of fibrosis in the lungs following administration of human mesenchymal stem cells (hMSC) to neonatal mice exposed to hyperoxia.MethodNewborn mice were exposed to 90% O2 (hyperoxia) or 21% O2 (normoxia) from postnatal days 0–4. A sub-group of hyperoxia mice were injected intratracheally with 2.5X105 hMSCs. Using flow cytometry we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Furthermore, the expression of their ligands, Csf1 and Ccl2, was upregulated in the hyperoxia-specific clusters Neutro.2 and Mac.4, respectively(Fig. 6h).These observations are consistent with the study by Kalymbetova et al, where Ccr2 -/and CSF1R-depleted mice developed milder structural changes in hyperoxia-exposed lungs50 .The cell count and transcriptional activity of Mac.3 cells (cluster 4), was stable in normal development, as well as after exposure to hyperoxia (Supplementary Figure 6a-c), and expressed high levels of inflammatory mediators, consistent with data by Gibbings et al51 (Supplementary Figure 6k).The concept of M1/M2 polarization of macrophages has been linked to normal development, as well as to several lung pathologies, including BPD2,52,53 . Consistent with previous studies, our results suggested that the expression of M2 genes was increased in alveolar macrophages during postnatal development 2(Supplementary Figure 6l).Furthermore, hyperoxia enhanced the M1 signature of Mac.2 macrophages and induced a new population of macrophages -Mac.4characterized by the activation of both M1 and M2 genes (Supplementary Figure 6m).…”
supporting
confidence: 84%
“…Furthermore, the expression of their ligands, Csf1 and Ccl2, was upregulated in the hyperoxia-specific clusters Neutro.2 and Mac.4, respectively(Fig. 6h).These observations are consistent with the study by Kalymbetova et al, where Ccr2 -/and CSF1R-depleted mice developed milder structural changes in hyperoxia-exposed lungs50 .The cell count and transcriptional activity of Mac.3 cells (cluster 4), was stable in normal development, as well as after exposure to hyperoxia (Supplementary Figure 6a-c), and expressed high levels of inflammatory mediators, consistent with data by Gibbings et al51 (Supplementary Figure 6k).The concept of M1/M2 polarization of macrophages has been linked to normal development, as well as to several lung pathologies, including BPD2,52,53 . Consistent with previous studies, our results suggested that the expression of M2 genes was increased in alveolar macrophages during postnatal development 2(Supplementary Figure 6l).Furthermore, hyperoxia enhanced the M1 signature of Mac.2 macrophages and induced a new population of macrophages -Mac.4characterized by the activation of both M1 and M2 genes (Supplementary Figure 6m).…”
supporting
confidence: 84%
“…However, hyperoxia may promote inflammation, contribute to acute lung injury and impair antimicrobial immunity. Hyperoxia is thought to trigger a multicellular immune response, implicating monocytes, macrophages, neutrophils and NKT cells, as noted in separate studies [13][14][15][16][17][18] . However, a global view of the immune populations during hyperoxia has not been previously studied.…”
Section: Discussionmentioning
confidence: 90%
“…Pulmonary responses to hyperoxia likely involve multiple immune cell populations. Separate studies have reported that hyperoxia inhibits macrophage proliferation 13,14 , heightens the ratio of F4/80 low CD206 low (proinflammatory, "M1") to F4/80 high CD206 high (anti-inflammatory, "M2") alveolar macrophages 15 , and promotes influx of CD11b high CD11c low cells ("inflammatory monocytes") and CD11b high CD11c high macrophages ("exudative macrophages") into the bronchoalveolar space 16 . Increased infiltration of parenchyma by invariant NKT cells 17 and late recruitment of neutrophils 18 have also been described.…”
mentioning
confidence: 99%
“…At P14, the freshly excised lungs were placed into cold uorescence activated cell sorting (FACS) buffer (PBS containing 0.2% BSA, 0.02% NaN 3 and 5mM EDTA) for a maximum of 30 minutes. The main airways were removed and the lungs were cut into small pieces which were then digested mechanically and enzymatically as previously reported [18].…”
Section: Lung Preparation For Macrophage Isolationmentioning
confidence: 99%
“…In a recent study [18], we reported the therapeutic effects of human mesenchymal stem cells (hMSCs) on the polarisation of lung macrophages, the development of lung in ammation, and collagen deposition following hyperoxic lung injury in neonatal mice. To date, the therapeutic effectiveness of hMSCs on the gene expression of lung macrophages in response to hyperoxia, and the changes in total and small RNA associated with differing macrophage phenotypes, are yet to be determined.…”
Section: Introductionmentioning
confidence: 99%